Bank Branching Deregulation and the Syndicated Loan Market - Keil, Jan; Müller, Karsten (Journal of Financial and Quantitative Analysis, 2020)
How do changes in banking regulation affect the syndicated loan market? Because branch networks and loan syndication both enable banks to diversify geographical credit risk, we investigate the staggered implementation of the Riegle–Neal Interstate Branching and Banking Efficiency Act of 1994. Exploiting that the act only changed the legal framework for out-of-state commercial banks, we find that branching deregulation decreased syndicated loan issuance but spurred bilateral lending to corporations. Consistent with a supply-driven substitution effect, this shift is also reflected in interest rate spreads. Our results suggest that changes to banking regulation can substantially alter credit allocation across loan types.